On the relationship between political science and administrative science in Germany - Bogumil, Jorg (2005)
The theoretical and empirical analysis of administrative activities has been an important area of research since the establishment of political science as an academic discipline in Germany at the end of the 1960s. But is administrative science still a significant part of political science in Germany today? I argue here that in Germany a political science oriented administrative science has developed from a science focused on public administration, that is, on organizational questions, to one focused on public policies and thus on questions concernig the conditions and consequences of political problem solving and control (Steuerung). The question of the internal organization of government is increasingly irrelevant one; in addition, the institutional promotion and funding of political science administration research has dramatically decreased since the 1970s. Today's new challenges (economization and internationalization) for both government and public administration seem to exceed the capability of political science administrative research. These challenges open up new opportunities, however, since, in the search for solutions beyond the dichotomy of market/managerialism on the one hand and traditional bureaucracy and state government on the other, political science in particular regains more importance. As will be shown, there are now tendencies which indicate that political science administrative research might encounter a stronger political demand. If the consequent research is able to find a new mixture of theory and practice, this in turn could help revitalize political science administrative research in Germany. - Reproduced.
Keywords: Public administration - Germany; Public administration